2015
DOI: 10.1140/epjnbp/s40366-015-0027-z
|View full text |Cite
|
Sign up to set email alerts
|

BCI inside a virtual reality classroom: a potential training tool for attention

Abstract: Background: A growing population is diagnosed with Attention Deficit Hyperactivity Disorder (ADHD) and are currently being treated with psychostimulants. Brain Computer Interface (BCI) is a method of communicating with an external program or device based on measured electrical signals from the brain. A particular brain signal, the P300 potential, can be measured about 300 ms after a voluntary cognitive involvement to external stimuli. By utilizing the P300 potential, we have designed a BCI-assisted exercising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 27 publications
0
30
0
2
Order By: Relevance
“…10). This results can be associated with the improvement in evocation of ERPs in some healthy subjects, induced by training and increase in attention (Rohani and Puthusserypady, 2015).…”
Section: Erpsmentioning
confidence: 66%
See 1 more Smart Citation
“…10). This results can be associated with the improvement in evocation of ERPs in some healthy subjects, induced by training and increase in attention (Rohani and Puthusserypady, 2015).…”
Section: Erpsmentioning
confidence: 66%
“…A study performed by (Rohani and Puthusserypady, 2015) demonstrated the use of P300 speller as attention training system, showing that P300 is connected to attention in the healthy subjects. In the other recent study P300based speller BCI was used in neurofeedback training game, yielding in enhancement of ERP components, changing and increase in spatial attention tasks results (Amaral et al, 2015).…”
Section: P300 Bci For Cognitive Trainingmentioning
confidence: 99%
“…A research [40] is a treatment procedure for ADHD by designing an interface in assistance with P300 and VR, and achieved average error rate below 30%. In VR brain computer interface is a method, in assistance a system is designed with six subjects and achieved error rate below 0.30 [41]. Table 7 gives the Summary of ADHD using Virtual Reality.…”
Section: G Classification Of Applications Using Virtual Realitymentioning
confidence: 99%
“…The experiment regulates measurement collected from a particular electrode located on the scalp above the parietal lobe (Pz).To evoke P300 potential two arrangements of trials have been executed. One of the trial was operated the features of "P300 speller" and the second system applied in an environment where the user prerequisite was to explore a particular letter in a sessions of altering graphic images [15]. The compilation of results and feedback are accumulated from the healthy individuals who contributed in participating in the P300 based Virtual Reality system.…”
Section: Monitoring Through Cameramentioning
confidence: 99%